A Retrospective, Cross-Sectional, Descriptive Research: Evaluation of Traumatic Respiratory Impairment Cases That Were Sent to the Turkish Council of Forensic Medicine 3rd Speciality Board in 2020 - Efil, Hakan; Aydoğdu, Halil İlhan and İçmeli, Özlem Saniye and Küçük, Ceyhun and Bakır Küçük, Pınar (The Bulletin of Legal Medicine, 2023)
Objective: It is important to determine whether there is a long-term loss of respiratory function in people who have had thoracic trauma, both in respect of the clinical follow-up of cases and in judicial terms (punishment/compensation). The aim of this study was to examine the data related to the nature of trauma and sequelae associated with the respiratory disability of trauma origin, and by reviewing the basis of sequela evaluation, to contribute to future clinical studies to reduce morbidity in thoracic trauma patients and to specialists working in the field of disability. Methods: A retrospective review was performed by examining the medical records of cases with thoracic trauma referred for evaluation of disability following trauma (workplace accident, assault, traffic accident). The data were retrieved from the electronic database. Results: The ages of the cases included in the study ranged from 8 to 84 years, with a median age of 44. When the gender distribution was evaluated, it was seen that 85.3% of the cases were male (n=133), and 14.7% were female (n=23). As a result of all the evaluations, it was determined that 10 (6.4%) cases had a loss of pulmonary function due to thoracic trauma, and the disability rate was determined. Conclusion: As evaluation made on the basis of test results or examination findings alone when determining respiratory function losses can be erroneous, the decision must be made with examinations in specialized centers by experienced physicians guided by respiratory function tests and assistive and supportive imaging results.